Microconical Structure Formation and Field Emission From Atomically Heterogeneous Surfaces Created by Microwave Plasma–Based Low-Energy Ion Beams - Majumdar, Jayashree; Bhattacharjee, Sudeep (Frontiers in Physics, 2021)
We report formation of self organized micro-conical arrays on copper surface when exposed to high flux (5.4 x 10^15 cm^(-2) s^(-1)) of 2 keV argon ion beams at normal incidence. The created micro-conical arrays are explored for field emission properties. The surface morphologies are investigated by scanning electron microscopy and atomic force microscopy. The local work function variation is analysed by Kelvin probe force microscopy, and the argon content in the irradiated layer is measured with X-ray photoelectron spectroscopy. The average aspect ratio (base width/height) of microstructures for individual irradiated samples is found to increase from 0.7 to 1.5 with decrease in ion fluence. The ion concentration is highest (3.89 %) for fluence of 4.7 x 10^18 cm^(-2), which asserts the formation of atomically heterogeneous surface due to subsurface ion implantation. An enhancement in the field emission properties of the argon ion treated copper substrates at a fluence of 4.7 x 10^18 cm^(-2) with a low turn-on voltage of 2.33 kV with electron emission current 0.5 nA, has been observed. From the Fowler Nordheim equations, the field enhancement factor is calculated to be 5561 for pristine copper, which gets enhanced by a factor of 2-8 times for irradiated substrates. A parametric model is considered, by taking into account the modified local work function caused due to structural undulations of the microstructures and presence of implanted argon ions, for explaining the experimental results on field enhancement factor and emission current.